Fabrication and characterization of a titanium dioxide (TiO2) nanoparticles reinforced bio-nanocomposite containing Miswak (Salvadora persica L.) extract – the antimicrobial, thermo-physical and barrier properties - Ahmadi R (Dove Medical Press, 2019)
Raman Ahmadi,1 Asghar Tanomand,2 Fahimeh Kazeminava,1 Fadhil S Kamounah,3 Ali Ayaseh,4 Khudaverdi Ganbarov,5 Mehdi Yousefi,6 Adib Katourani,1 Bahman Yousefi,7 Hossein Samadi Kafil11Drug Applied Research Center, Tabriz University of Medical Sciences, Tabriz, Iran; 2Department of Basic Sciences, Maragheh University of Medical Sciences, Maragheh, Iran; 3Department of Chemistry, University of Copenhagen, DK- 2100 Copenhagen. Denmark; 4Department of Food Science and Technology, University of Tabriz, Tabriz, Iran; 5Department of Microbiology, Baku State University, Baku, Azerbaijan; 6Stem Cell Research Center, Tabriz University of Medical Sciences, Tabriz, Iran; 7Immunology Research Center, Tabriz University of Medical Sciences, Tabriz, IranObjective: The microbial, physico-chemical and optical corruptions threaten a variety of foods and drugs and consequently the human biological safety and its accessible resources. The humanbeing’s tendency towards bio-based materials and natural plant-extracts led to an increase in the usage of antimicrobial biocomposites based on medicinal herbs. Miswak (Salvadora persica L.) extract (SPE) has been proved effective for its antimicrobial and other biological activities. Therefore, in this study, titanium dioxide (TiO2) nanoparticles (TONP) and SPE were applied to fabricate antimicrobial carboxymethyl cellulose (Na-CMC) based bio-nanocomposites which would simultaneously promote some thermo-physical and barrier properties.Methods: CMC-neat film (C1), CMC/TONP-2% (C2) and CMC/TONP-2% with 150, 300 and 450 mg/mL SPE (SPE150, SPE30 and SPE450, respectively) were fabricated. The physical and mechanical properties; elemental mapping analysis (MAP), X-ray diffraction (XRD), scanning electron microscopy (SEM), thermal gravimetric analysis (TGA-DTG); fourier transform infrared (FTIR), energy-dispersive X-ray (EDX) and UV-vis spectroscopies were done to further validate the results.Results: Addition of TONP (2%) improved the blocking of UV light at 280 nm while SPE-containing nanocomposites completely blocked it. FTIR, XRD and SEM confirmed the formation of homogeneous films and high miscibility of applied materials. TONP led to an increase in Young’s modulus (YM) and stress at break (SB) while SPE decreased them and enhanced the elongation to break (EB) (flexibility) of the active nanocomposites. Compared to CMC-film, the thermo-gravimetric analysis (TGA-DTG) showed a higher thermal stability for CMC/TONP and CMC/TONP/SPE nanocomposites. The EDX spectroscopy and elemental mapping analysis (MAP) proved the existence and well-distributedness of Na, K, Cl, S, Ti, F and N elements in SPE-activated nanocomposites. The pure SPE and SPE-activated nanocomposites showed a favorable antimicrobial activity against both gram-positive (Staphylococcus aureus) and negative (Escherichia coli) bacteria.Conclusion: The CMC-TiO2-SPE nanocomposites were homogeneously produced. Combination of TiO2 nanoparticles and dose-dependent SPE led to an improvement of thermal stability, and high potential in antimicrobial and UV-barrier properties. These results can generally highlight the role of the fabricated antimicrobial bio-nanocomposites as a based for different applications especially in food/drug packaging or coating.Keywords: antimicrobial biomaterials, biopolymeric nanocomposite, carboxymethyl cellulose, Miswak (Salvadora persica L.), titanium dioxide, food packaging